A small switch in perspective: Comparing weight loss by nutrient balance versus caloric balance - Clark, James E. (Biology of Sport, 2024)
The establishment of a Caloric balance has been classically discussed as the means to induce weight loss. Recently, the idea of nutrient balance as opposed to Caloric balance has emerged as a better means to induce weight loss. This investigation compared differences in weight loss between a diet based on a nutrient balanced diet compared to a Caloric balance diet. 53 (27M/26F) active overfat individuals (30.7+/- 7.1 years) were randomly (matched for age, gender, training history) assigned within an 8-week intervention to follow either a self selected diet (control) or a diet based on following a Caloric balance (%Cal/day) or a nutrient balance (g/kg/day) in conjunction with a periodized exercise regimen to determine effectiveness for each diet to induce weight loss. Nutrient balance group had significantly different changes ( p < 0.05) in fat-free mass (2.26 (2.02, 2.49) kg versus 0.42 (-0.40, 1.24) kg) and fat mass (-5.96 (-5.34, -6.58) kg versus -4.08 (-3.92, -5.92) kg) relative to the Caloric balance group and was more effective at meeting nutritional requirements for protein (ES = 0.65 (0.48, 0.85)) and lipids (ES = 0.24 (-0.09, 0.98)) than the Caloric balance group. Nutrient balance was subjectively scored as easier to follow and more likely to be self selected. Using a nutrient balance diet may be more effective at inducing beneficial body compositional changes and shows being a more self-selected dietary method when compared to a Caloric balance diet. Therefore, it may be a better choice for advice when offering treatments to those who are attempting to lose weight or maintain weight loss.